TOTAL FLAVONOID LEVELS AND ANTIOXIDANT ACTIVITY OF KERSEN LEAF EXTRACT (muntingia calabura L.) - L A, Hamdayani; Fitriyanti Jumaetri Sami; Yuri Pratiwi Utami (JURNAL KATALISATOR, 2024)
Kersen leaves (Muntingia calabura L.) are plants that contain many secondary metabolites, one of which is flavonoids that can act as antioxidants. This study aims to determine the total content of flavonoids which also have the potential as antioxidants in cherry leaves using the DPPH method (2,2-diphenyl-1-picrylhidrazyl) with various filters, namely 70% ethanol, ethyl acetate and n-hexan. Testing of total flavonoid content was carried out using AlCl3 reagent and measured using spectrophotometry at a wavelength of 422 nm. Antioxidant activity testing was measured at an absorption wavelength of 516 nm. The results showed the total flavonoid content of 70% ethanol filter leaf extract as much as 8.13 (mgQE/g), ethyl acetate as much as 8.32 (mgQE/g) and n-hexan as much as 18.96 (mgQE/g). antioxidant activity of cherry leaves using DPPH method (2,2-diphenyl-1-picrylhidrazyl) with filter variations. 70% ethanol extract of cherry leaves has an IC50 value of 7.56 μg/mL, ethyl acetate extract with an IC50 value of 36.05 μg/mL, and n-hexan extract with an IC50 value of 21.33 μg/mL. From the results obtained it can be concluded that the highest antioxidant activity is contained in 70% ethanol extract of 7.56 μg/mL.